2012
DOI: 10.1073/pnas.1208214109
|View full text |Cite
|
Sign up to set email alerts
|

Position-dependent correlations between DNA methylation and the evolutionary rates of mammalian coding exons

Abstract: DNA cytosine methylation is a central epigenetic marker that is usually mutagenic and may increase the level of sequence divergence. However, methylated genes have been reported to evolve more slowly than unmethylated genes. Hence, there is a controversy on whether DNA methylation is correlated with increased or decreased protein evolutionary rates. We hypothesize that this controversy has resulted from the differential correlations between DNA methylation and the evolutionary rates of coding exons in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 43 publications
5
49
2
1
Order By: Relevance
“…In line with other studies (23,24), we observe negative correlations of CpGs with gene expression close to the transcription start sites and an increasing proportion of positive correlations in proximal and distal regulatory sites ( Fig. 2B and Dataset S5).…”
Section: Correlation Of Gene-expression Differences With Dna Methylationsupporting
confidence: 79%
“…In line with other studies (23,24), we observe negative correlations of CpGs with gene expression close to the transcription start sites and an increasing proportion of positive correlations in proximal and distal regulatory sites ( Fig. 2B and Dataset S5).…”
Section: Correlation Of Gene-expression Differences With Dna Methylationsupporting
confidence: 79%
“…We include the first exon in our definition of a promoter because recent studies have shown that the transcriptional effect of methylation typically extends to and includes the first exon (52). In addition, first exons exhibit computational and evolutionary properties that are consistent with promoters (53,54). We also obtained whole-genome bisulfite-sequencing data of the human placenta from ref.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the DNA methylation level is correlated with the biological and evolutionary features of coding exons in different genic positions (Chuang et al 2012 ). 5-Methylcytosine (5mC) The mammalian circadian clock is composed of a transcriptional activation feedback loop of ~24 h. RNA Pol II, which is phosphorylated on serine 5 in the carboxyl-terminal heptapeptide repeat domain (CTD) (Pol II S5P), is paused on promoter proximal sites of circadian clock genes at circadian time (CT) 0 and CT23-24 (Adelman and Lis 2012 ).…”
Section: Dna Methylation Determines Cell Type Specifi Citymentioning
confidence: 99%